Information-seeking behavior of UP College of Law students - Implica, Merry Joy S. (2010)
We are in the digital era where information can be acquired anywhere. The emergence of the Internet somehow might change the information-seeking behavior of the society. Information-seeking behavior is actions done by a person when in need of information. This study aims to have a better understanding of the information-seeking behavior of UP College of Law students. This study also intends: to determine the techniques used by UP Law students when seeking information; to know if there is a relationship between the students personal characteristics and their preferred techniques in the following information seeking phases: Starting, Chaining, Browsing, Differentiating, Monitoring, Extracting, Verifying and Ending (Ellid, 1998); to determine the issues and concerns encountered by the students in accessing the library; and to ascertain the different ways by which the UP Law Library Management addresses the problems encountered by the students. This study employed survey questionnaire. Two hundred questionnaires were distributed to UP Law students but only 157questionnaires were returned.